Five ways satellite images, remote sensing and smartphones are combining to transform agriculture - Ghosh, Aniruddha; Koo, Jawoo (CGIAR System Organization, 2022)
From satellites launched into low orbit, to smartphones spreading across the developing world, each day the Earth is pictured in greater detail and frequency than before. Researchers are continually finding new ways to use these images to increase agricultural productivity and resilience to climate change, every method has its drawbacks and challenges, especially when it comes to smallholder farming. Here are five ways in which different technologies are being combined to transform agriculture in rural areas of Africa, Asia and Latin America.